Multidisciplinary Management of Complicated Crown-Root Fracture: A Case Report - Zahra Enshaei; Maede Ghasemi (Tehran University of Medical Sciences, 2018)
The management of traumatic dental injuries as well as crown-root fractures is always challenging in everyday general dental practice. A number of treatment modalities are available for crown-root fractures, depending on the position, extent and severity of the fracture. The aim of this case report was to describe a clinical case of rehabilitation of a complicated crown-root fracture of the maxillary left central incisor, successfully treated by a multidisciplinary approach including orthodontic extrusion. The final result was esthetically pleasant and periodontally sound in the follow ups.